Protein phosphatase AP2C1 negatively regulates basal resistance and defense responses to Pseudomonas syringae - Shubchynskyy, Volodymyr (Journal of experimental botany, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology.